Enhancing Wear Resistance of Brass Composites Using Fly Ash Reinforcement: A Specific Weight Loss Study - Aminnudin, Aminnudin; Suryanto, Heru; Ghazali, Che Mohd Ruzaidi; Setiawan, Danni Dwi (Engineering, Technology & Applied Science Research, 2026)
Metal Matrix Composites (MMCs) with a brass matrix reinforced by coal-derived fly ash present a promising alternative to conventional brass. The addition of fly ash improves the material properties; however, its effect on the wear resistance of brass-based MMCs remains insufficiently studied. This study investigates the specific weight loss behavior of brass composites with varying fly ash content. In this study, MMCs were fabricated using the stir casting method in a gas furnace with varying fly ash contents of 5%, 10%, 15%, and 20% by weight. Brass was used as the matrix material. Hardness tests of the resulting composites were performed using the Rockwell-B hardness test method. Wear testing was conducted utilizing the pin-on-disk method, applying a load of 1000 grams. Tests were carried out at sliding distances of 600, 800, and 1000 m. The results showed that the addition of fly ash significantly affected both hardness and wear resistance. The MMCs with 5% fly ash exhibited the highest hardness value of 78 HRB and the lowest specific weight loss of 0.055 mg/m, indicating better wear resistance compared to the MMC without fly ash. Increasing the fly ash content beyond 5% led to a gradual decrease in hardness and an increase in weight loss.